Awards, honors, and prizes : Adirctory and source book (Detroit : Gale Research Co., 1969)
Listing and description of 2228 awards, honors, and prizes given for outstanding achievement in the United States and Canada. Science, technology, and medicine are among the 28 broad fields covered. Main listing by organization, with address and annotation. Alphabetical index of awards, subject index of awards.
3rd ed.- issued in two vols.: v. 1, United States and Canada; v. 2, International and foreign awards.
Also issued online.
Latest issue consulted: 8th ed.
SERBIB/SERLOC merged record
Keywords: Directory; Directories